Time scales based analysis of the effects of COVID-19 related economic support on the stock markets in emerging markets - Melik Kamişli; Mustafa Özer; Özlem Sayilir; Patrice Racine Diallo (Journal of Central Banking Theory and Practice, 2023)
The main purpose of this study is to investigate the causalresponse of the stock market returns to COVID-19 related economicsupport in 19 emerging countries by using the Maximal Overlap Dis-crete Wavelet Transform (MODWT) and Fourier Toda-YamamotoCausality Test (FTYCT). With the help of MODWT, we identify theinstant, short-term, mid-term and long-term reactions of stock mar-ket returns and COVID-19 related economic support to each other.Implementing FTYCT, we determine the existence of the causal re-lationships running from COVID-19 related economic support tostock returns. We obtain two major results. First, the COVID-19related economic support have significant effects on stock marketreturns in the short-, medium-, and long-term, except in China. Sec-ond, the results of the causality tests vary across countries based onthe different time scales. Some emerging markets show an immedi-ate reaction to the Economic Support, while most stock market reac-tions occur over the medium- and long-term. Since economic sup-port will created unintended effects on stock market returns, the waythat these support policies are implemented should be reconsidered.Also, their effectiveness should be evaluated carefully.
Keywords: C58; G01; G15; 330; COVID-19 related economic support; stock market re-turns; emerging markets; time scales wavelet transform; FourierToda-Yamamoto causality test